Doctors’ Comunication Style: Impact on Patients Participation (Sains Humanika, 2013)
This paper presents the findings of a study on doctors’ communication style and its implications on patients’ participation. The data for this study were gathered from audio recording of ten clinical consultations and interview with a doctor at the Hematology Clinic in a General Hospital in Malaysia. The data were transcribed and analysed based on the three components of patients’ participation proposed by Cegala (2011). Findings indicate doctors display two different styles of communication during the clinical consultations. Further investigation reveal that the sharing style consultation does indeed encourage more patients’ participation than the Directing style. The findings of this study have important implications for communication training for medical students. The paper concludes with a discussion of the directions for future studies.
Keywords: Doctor communication style; sharing style; directing style; patient participation; health communication